STRATEGI PENINGKATAN DAYA TARIK PRODUK PADA INDUSTRI MAKANAN (Studi Kasus Kerupuk Beras Ibu Lilis di Tenggarong) - Kurnia Warni, Dea; Noorhya Akhmar Ramadhan Putri, Eva; Dewi, Septira (I-Con Media, 2025)
The purpose of this study was to determine and assess the condition of Mrs. Lilis Rice Crackers Business in Tenggarong from the position of strengths, weaknesses, opportunities and threats and to find out the right strategy to be applied to Mrs. Lilis Rice Crackers Business in Tenggarong. This study uses quantitative data obtained from questionnaire data. The number of research samples was 100 people with the method of taking random sampling. The analysis tool uses SWOT analysis. Based on the SWOT matrix, it is obtained that the current position / strategy of Mrs. Lilis' Rice Crackers Business in Tenggarong is a stabilization / turn around strategy located in quadrant III, meaning that the company faces enormous market opportunities, but on the other hand Mrs. Lilis' Rice Crackers Business faces several internal weaknesses. The focus of the strategy that must be applied in this condition is to minimize the company's internal problems so that it can seize better market opportunities. Alternative strategies that can be carried out by Mrs. Lilis Rice Crackers Business in Tenggarong by looking at its position, namely the WO (weaknesses - opportunities) combination are as follows a. promotion using social media, b. adding stock variations of product results, c. expanding the distribution network with delivery services, d. Increasing business capital with low-interest bank loans, dan e. increase product shelf life